HIV negative polycystic lymphoepithelial cyst of parotid gland: A case report and literature review - YANG Zhenglin; LUO Feiyang; YANG Sen (Kouqiang hemian waike zazhi)
Lymphoepithelial cyst (LEC) of the parotid gland is a rare lesion and easily misdiagnosed in clinic, it should be differentiated with a variety of parotid gland cystic diseases. LEC is considered to be the most common cause of parotid gland enlargement in human immunodeficiency virus (HIV)-positive patients, while its proportion is extremely low in HIV-negative parotid neoplasms. HIV-negative LEC patients are most likely to present as unilateral and unilocular parotid gland lesion, while bilateral or polycystic LEC of parotid gland is mostly seen in HIV-infected patients. Currently, there are a variety of treatment methods for LEC. With the literature review, we believe that surgical resection is the preferred treatment method for LEC, sclerotherapy and antiretroviral therapy are of great significance for HIV-positive patients, while conservative observation can be taken for those without treatment intentions. Recently, a HIV-negative patient with unilateral polycystic parotid LEC was admitted to our department, which is extremely rare in clinic and the report is as follows.